2006
DOI: 10.4067/s0716-97602006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is closely related to clinical severity of pre-eclampsia

Abstract: Pre-eclampsia is a hypertensive disorder of pregnancy in which enzymatic antioxidant defenses fail and tissues are injured. This prospective case-control study evaluated whether pre-eclamptic women and their newborns show higher degrees of oxidative stress than normal pregnancies and sought to determine if this stress is related to clinical severity. Forty-four pre-eclamptic and thirty healthy pregnant women attending two hospitals in Valparaíso, Chile, were studied. The following plasmatic variables of antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 14 publications
3
46
2
1
Order By: Relevance
“…In India, studies conducted by Adiga, Patil et al [5] and Krishna Menon S [6] at different institutes showed significant elevations in the levels of malondialdehyde in preeclampsia compared to normal pregnancy and nonpregnant females. Outside India also, various studies like those by Elesa Llusla [7], Madazli R et al, and Chamy et al [8] have all found significantly increased MDA levels in preeclampsia as compared to normal pregnancy and also in pregnancy as such compared to non-pregnant females.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…In India, studies conducted by Adiga, Patil et al [5] and Krishna Menon S [6] at different institutes showed significant elevations in the levels of malondialdehyde in preeclampsia compared to normal pregnancy and nonpregnant females. Outside India also, various studies like those by Elesa Llusla [7], Madazli R et al, and Chamy et al [8] have all found significantly increased MDA levels in preeclampsia as compared to normal pregnancy and also in pregnancy as such compared to non-pregnant females.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…The two hallmark symptoms are hypertension and proteinuria, complicating at least 5% of pregnancies and are usually resolved upon delivery of the placenta. Preeclampsia has been closely associated with oxidative stress in a number of studies [1][2][3][4]. The mechanism of oxidative stress associated hypertension has been continuously evolving with the popular theme of endothelial dysfunction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study decreased activity of catalase was noted by others. 6,13,14 Catalase is the enzyme which protects the cells from the accumulation of hydrogen peroxide by dismutating it to water and oxygen or by using it as an oxidant in which it works as peroxidase. 14,15 In contrast to our study, few others reported increased activity of catalase enzyme in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 In contrast to our study, a decrease in GPx activity in preeclampsia was noted by others. 5,6,17 Glutathione peroxidase (GPx), an oxidative stress inducible enzyme plays a significant role in the peroxyl scavenging mechanism and in maintaining functional integration of the cell membranes. 21 The rise in the activity of this antioxidant enzyme could be due to its induction to counter the effect of increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation